The effect of fungicides on the physiological and biochemical state of lupine plants after seed treatment - Borzykh, O.; Tsurkan, O.; Chervyakova, L.; Panchenko, T. (Quarantine and plant protection, 2023)
Goal. To assess the effect of fungicides on the content of chlorophyll and the activity of antioxidant enzymes (peroxidase, catalase) in lupine plants after seed treatment. Methods. Laboratory and vegetation studies were carried out in the laboratory of analytical chemistry of pesticides of pesticides of the Institute of Plant Protection. The seeds of yellow lupine (Lupinus luteus L., variety Obriy) were treated with combined fungicides from different chemical classes: triazoles (cyproconazole, difenoconazole, tebuconazole, prothioconazole), phenylpyrroles (fludioxonil), carboxamides (carboxin), dithiocarbamates (thiram). Determination of the content of fungicides in plants was carried out using chromatographic methods of analysis. Chlorophyll content, peroxidase and catalase activity were determined by physicochemical methods according to generally accepted methods. Results. Fungicides activated the antioxidant systems of plants, depending on their physicochemical properties (in particular, the octanol-water partition coefficient Kow) and their content in plants (C, mg/kg). An increase in peroxidase activity (up to 89% compared to the control) was established within 30 days, which indicates the activation of antioxidant processes aimed at maintaining oxidative homeostasis in plants. The change in catalase activity under the influence of fungicides was inversely correlated with peroxidase activity, which is explained by the formation of adaptive mechanisms of ROS homeostasis. The high activity of peroxidase, compared to catalase, testifies to the important role of this enzyme in the redox reactions of plant resistance under the influence of fungicides. The total chlorophyll content under the action of fungicides, increased by 6—20%, compared to the control. Conclusions. Seed treatment with fungicides affects the course of redox reactions in plants, causing changes in the activity of key enzymes. The high activity of peroxidase against the background of fluctuations in catalase activity indicates the direct effect of fungicides on the state of antioxidant systems and the important role of peroxidase in maintaining ROS homeostasis. The stimulatory effect of fungicides on the accumulation of chlorophyll at the initial stages of growth of lupine plants was established, the content of which exceeded the control indicator by 6—20% by development phase. Changes in the activity of antioxidant enzymes (catalase and peroxidase) and the content of chlorophyll can serve as criteria for determining the levels of adaptation of lupine plants to the stress effect of fungicides.